On the pricing effects of bitcoin mining in the fossil fuel market: The case of coal - Sibande, Xolani; Demirer, Riza; Balcilar, Mehmet; Gupta, Rangan (Elsevier Sci Ltd, 2023)
This study provides novel insight to the role of cryptocurrency mining activities on fossil fuel price dynamics with a particular focus on the coal market. Despite the global climate agenda, coal remains a key energy source for economic growth as it is the dominant fuel for power generation globally. At the same time, the unprecedented growth in the trading and mining of cryptocurrencies has put extra pressure on this market as the mining process consumes vast amounts of energy fuelled predominantly by coal. Hypothesizing that there is a causal link in the direction of coal prices from Bitcoin mining activities due to its effect on electricity consumption, we utilize static and time-varying Granger causality tests to explore the causal linkages between Bitcoin electricity consumption and coal prices as the issue has significant implications for economic development. The results reveal a time-varying causal link from the coal price to Bitcoin mining electricity consumption, suggesting that the coal price is in fact a constraint on mining activities. At the same time, as hypothesized, the evidence in the opposite direction is found to be even stronger, suggesting that electricity consumption from Bitcoin mining activities impacts the coal price. This interplay suggests that electricity consumption from Bitcoin mining activities may be larger than current estimates, highlighting the importance of policy mechanisms to mitigate the possible negative effects on the economy.
Keywords: Time-varying granger causality; Crypo-currency market; Commodity markets